Determnation of general condition and nutritive value of The fishes Liza abu in Dijila river: Layla.M.Z.AL-kinani , Nuhad Abud AL-mahdi - AL-kinani, Layla M.Z. (The Iraqi Journal of Veterinary Medicine, 2005)
From dijila river ,weakly five fishes liza abu were caught for aperiod ofsix month. For (120) liza abu afull sensitive investigations were carried out(general conditions , PH , nutritive value). Investigation results indicated that;The general condition averagad 0.96 and the calorific value averaged (167.45kcal/100g ). The main length & wight were (21.79)cm and 100.32gmrespectively . The main value of moisture , protein , fat , ash ,dry matter ,organicmatter , nitrogen free extract and crude fiber were 72.5% , 16.48% ,7.2% ,1.3%,27.5% ,26.2% ,2.5% respectivelyConclusionThere were no significant differences in the result of the investigation carriedduring experimantel period.